2020
DOI: 10.3390/ijerph17165642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Sediment Organic vs. Mineral Content on Distribution of the Per- and Polyfluoroalkyl Substances (PFAS) in Lake Sediment

Abstract: Contamination of the water and sediment with per- and polyfluoroalkyl substances (PFAS) was studied for the lake impacted by the release of PFAS-containing aqueous film forming foam (AFFF). PFAS concentrations were analyzed in lake water and sediment core samples. ΣPFAS concentrations were in the range of 95–100 ng L−1 in the lake water and 3.0–61 µg kg−1 dry weight (dw) in sediment core samples, both dominated by perfluorohexane sulfonate, perfluorooctane sulfonate; 6:2 fluortelomer sulfonate was inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Here, the authors identified eight different PFAS in the lake water, and thirteen PFAS in the sediment samples, ranging from 95-100 ng/L and 3-61 ng/g dw, respectively. In both the cases, the PFAS composition was markedly dominated by PFOS and PFHxS [120]. In another report, by using liquid chromatography tandem mass spectrometry (LC-MS/MS), Guo et al analyzed the concentration of PFSAs PFCAs, PFPIAs and PFPAs from sediment cores of distinct lakes in the Great Lakes Region, revealing that the highest contamination level occurred in the Ontario lake (sum of PFAS equal to 13.1 ng/g), where PFOS contributed over 80% of the total content [121].…”
Section: Pfas Occurrence In Freshwater and Sedimentsmentioning
confidence: 95%
“…Here, the authors identified eight different PFAS in the lake water, and thirteen PFAS in the sediment samples, ranging from 95-100 ng/L and 3-61 ng/g dw, respectively. In both the cases, the PFAS composition was markedly dominated by PFOS and PFHxS [120]. In another report, by using liquid chromatography tandem mass spectrometry (LC-MS/MS), Guo et al analyzed the concentration of PFSAs PFCAs, PFPIAs and PFPAs from sediment cores of distinct lakes in the Great Lakes Region, revealing that the highest contamination level occurred in the Ontario lake (sum of PFAS equal to 13.1 ng/g), where PFOS contributed over 80% of the total content [121].…”
Section: Pfas Occurrence In Freshwater and Sedimentsmentioning
confidence: 95%
“…The distribution of long-chain PFAS is inuenced by both moisture and DOM in the solid medium. 49,[61][62][63][64][65][66][67] Interestingly, DOM at 2  depth (7.82-14.21 g kg −1 ) was signicantly (a # 0.05) greater than the DOM at the compost surface (3.57-4.78 g kg −1 ), showing a strong correlation with the total PFAS at varying depths (Tables S12, S13 and Fig. S5 †).…”
Section: Vertical Distribution Of Pfas In a Compost Storage Pilementioning
confidence: 99%
“…Mussabek et al found that the sorption onto sediment of PFC also depends on the mineral contents in sediment such as metal ions. Their study explored that the correlation between PFCs concentration and sediment elemental content, in which a possitve correaltion was found between PFOS and lead, arsenic, iron contents, PFOA and lead, arsenic, titanium in sediment (Mussabek et al 2020). It suggests that we need more detailed studies on the effecet of inorganic contents on the distribution of PFCs in sediment.…”
Section: The In Uences Of Sediment Properties On the Adsorption Onto Sedimentmentioning
confidence: 99%